The costs and benefits of governing in a multi-level system - Matthias Scantamburlo; Davide Vampa; Ed Turner (Political Research Exchange)
In recent years the ‘cost of governing’ has significantly increased for some mainstream political parties. In a context of financial uncertainty, multiple crises and growing constraints exerted by global forces, being a ‘natural’ party of government is no longer regarded as an electoral advantage. This is particularly true for parties that have moved from a position of clear dominance within ruling coalitions to a more subordinate role. In this article, focusing on the Social Democratic Party of Germany (SPD) and using an original dataset, we aim to provide a more nuanced assessment of the effects of incumbency by examining regional electoral performance since 1990. It appears that sub-national incumbency can be beneficial in regional elections, especially when a party faces significant costs of governing at the national level. However, this advantage is only applicable if the party holds a leading position in the regional executive. On the contrary, being a junior coalition partner at both national and regional levels may further exacerbate electoral decline for the party.